Infiltrative lamina propria invasion pattern as an independent predictor for cancer‐specific and overall survival of instillation treatment‐naïve stage T1 high‐grade urothelial bladder cancer. (22nd February 2018) - Otto, Wolfgang; van Rhijn, Bas WG; Breyer, Johannes; Bertz, Simone; Eckstein, Markus; Mayr, Roman; Lausenmeyer, Eva M; Denzinger, Stefan; Burger, Maximilian; Hartmann, Arndt
Abstract : Objectives: To investigate established prognostic factors and relatively new histopathological tumor characteristics including metric substage and lamina propria invasion patterns in a large series of T1 high‐grade non‐muscle‐invasive bladder cancer. Methods: Between 1989 and 2012, 322 patients with initial stage T1 high‐grade bladder cancer underwent transurethral resection, followed by re‐transurethral resection and a conservative approach with follow‐up regime alone or instillation treatment. Transurethral resection specimens were reassessed by two experienced urological pathologists for tumor grade according to the World Health Organization 1973 classification, metric T1 substage, lamina propria invasion pattern and associated carcinoma in situ . The median follow‐up period was 42 months (interquartile range 25–72 months). In addition to Kaplan–Meier analyses, uni‐ and multivariable Cox regression analyses were used to compare progression‐free survival, cancer‐specific survival and overall survival for the studied parameters comparing two subcohorts. Results: While in patients after instillation treatment no examined feature was shown as an independent predictor for prognosis, there were predictive histopathological features in multivariable Cox regression analyses in instillation treatment‐naïve patients: associated carcinoma in situ (hazard ratio 2.278, 95% confidence interval 1.119–4.634, P  = 0.023) and World Health Organization 1973 grade 3 (hazard ratio 2.950, 95% confidence interval 1.021–8.536, P  = 0.046) for worse progression‐free survival, infiltrative lamina propria tumor pattern for worse cancer‐specific survival (hazard ratio 2.369, 95% confidence interval 1.034–5.429, P  = 0.042) and overall survival (hazard ratio 1.049, 95% confidence interval 1.024–1.075, P  = 0.001). Conclusions: The results of the present T1 high‐grade bladder cancer series suggest that lamina propria invasion pattern is a promising parameter to predict the prognosis of T1 high‐grade bladder cancer in an instillation treatment‐naïve subcohort. Prospective multicenter evaluations are warranted. The need for instillation treatment in T1 high‐grade bladder cancer is clearly demanded.